HISTIA: NAVAL HISTORY AND TEXTILE ARCHAEOLOGY. INVESTIGATING THE SAILS OF THE ANCIENT RHODIAN NAVY - Manolis I. STEFANAKIS; Stella SPANTIDAKI; Ioannis MPARDANIS (Journal of Ancient History and Archaeology)
The paper discusses the methodology, some preliminary results and scientific problems of the HISTIA research project studying the production, maintenance, and administration of a neglected area of research, namely the sails, rope and any textile equipment needed for the military ships of Rhodes, mainly based on similar studies carried out for the Athenian navy, as well as research on the naval power of Rhodes. By focusing on this previously unstudied field of naval studies, this project, not only aims at breaching a significant research gap, but also establishes a new field of textile archaeology that studies textiles intended for the ships.